(3QYGjI GdeJahbjf ef efXhQ ESdGej hGfYcGSGJgG GdJQHhjI (B/s - (3WhGdHI, NGdO YHO GdQMef CMeOs; (3eQcR LeYI GdeGLO ddKbGaI hGdJQGK(B.s (3bSe GdOQGSGJ hGdfTQ hGdTDhf GdNGQLjIs ((3OHj, GdEeGQGJ GdYQHjI GdeJMOI (B:s (3eQcR LeYI GdeGLO ddKbGaI hGdJQGK,s, 2011)
(3JfGhd cJGH (B((3QYGjI GdeJahbjf ef efXhQ ESdGej hGfYcGSGJgG GdJQHhjI(B)(3, ddcGJH NGdO YHO GdQMef CMeO WhGdHI, Yf eQcR LeYI GdeGLO ddKbGaI hGdJQGK, HeQGLYI hOQGSI bSe GdOQGSGJ hGdfTQ hGdTDhf GdNGQLjI aj GdeQcR(B. (3hjJVef GdcJGH (B: (3eLehYI ef GdCHMGK GdeYebI, efgG (B: (3eaghe GdJahb hejGOjfg hNUGFU GdeJahbjf hCgejI QYGjJge, eXGgQ GgJeGe GdESdGe HGdJahb, OhQ GdCSQI hGdeOQSI aj QYGjI GdeJahbjf(B. (3ceG COQL GdeDda YOI NUGFU ddeJahbjf, eKd (B: (3SQYI GdGSJLGHI dChGeQ Gddg JYGdi, GdJYde HSQYI hSghdI hJecf hEJbGf, GdMaX hGdGSJXgGQ hbhI GdPGcQI, MH GdGSJWdGY(B.s
(3GdCUd CWQhMI eGLSJjQ, LGeYI GdjQehc, (B2007.s
(3HHdjhLQGajI (B: (3UaMI (B281-296.s
Keywords: (3GdESdGe hGdehghHjfs -- (3JYdjes -- (3GdESdGe hGdeJahbjfs -- (3GdehghHjf hGdeJahbjfs -- (3JQHjI ESdGejIs